The initial intravenous treatment of a human immunodeficiency virus-infected child with complicated abdominal tuberculosis - Anthony K. Enimil (Southern African Journal of HIV Medicine, 2020)
Introduction: There is very limited published experience with intravenous (IV) antituberculosis (anti-TB) and antiretroviral therapy (ART) especially in children. We have described a human immunodeficiency virus (HIV)-infected child with complicated abdominal tuberculosis who was initially treated with IV anti-TB and a partially IV ART regimen before transitioning to oral therapy.